DIGITAL BROADCAST RECEIVER - FUKUI YUICHI (2016)
PROBLEM TO BE SOLVED: To provide a digital broadcast receiver capable of securing storage capacity by deleting a broadcast managed application which does not have a schedule of going to a use place thereof when acquiring the broadcast managed application.SOLUTION: A digital broadcast receiver 5 comprises: a reception part 10 which receives a digital broadcast; a communication part 31 which downloads a broadcast managed application; an area specification part 51 which specifies a use region of the application; a broadcast managed application management part 54 which manages the application and application information including a use region and a terms of validation thereof; a schedule management part 52 which manages schedule information including a region and a date of a schedule visit; and a storage part 32 which stores the application and respective information. The broadcast managed application management part deletes a broadcast managed application not to be used in a use region within a term of validity from the storage part.SELECTED DRAWING: Figure 1 【課題】放送マネージドアプリケーションを取得した場合、その使用地域に行く予定がないものを削除して記憶容量を確保できるデジタル放送受信機を提供する。【解決手段】デジタル放送受信機５は、デジタル放送を受信する受信部１０と、放送マネージドアプリケーションをダウンロードする通信部３１と、そのアプリケーションの使用地域を特定する地域特定部５１と、そのアプリケーションと、その使用地域及び有効期限を含むアプリケーション情報を管理する放送マネージドアプリケーション管理部５４と、訪問予定の地域と日付を含むスケジュール情報を管理するスケジュール管理部５２と、アプリケーションや各情報を記憶する記憶部３２とを備える。放送マネージドアプリケーション管理部は、有効期限までに使用地域で使用することのない放送マネージドアプリケーションを記憶部から削除する。【選択図】図１